A caridade é, em tudo, a regra de proceder: análise do discurso espírita kardecista - Silva, Tamiris Vianna da [UNESP] (2014)
In this work, we analyze the Kardecist spiritist discourse, as it is currently circulating in Brazil, from the perspective of the Discourse Analysis of the French line, emphasizing reflections of Maingueneau (2008) on the notion of global semantics. From this point of view, discourse is considered as a system of semantic constraints which restricts all levels of speech (vocabulary, topics discussed, intertextuality, instances of enunciation) at the same time. This restriction system does not concern only verbal speech production but also makes it commensurable with the institutional network of the group that the enunciation of discourse presupposes and at the same time makes it possible. Thus, we analyzed the Kardecist spiritist discourse considering it as a discursive practice, in terms of Maingueneau (2008), in order to highlight the radical overlap between the verbal face and the social face of the discourse. For the development of the analysis, we organized a very diverse corpus, which includes different genres of verbal-visual nature, which does not cease to be a reflection of the diversity of production related to the spiritist speech. The guiding principle of analysis is the evaluation of the hypothesis formulated about this speech, that is, the trait/+Christianity/ is one of semantic features of its system of global semantic constraints. From our point of view, this trait does not exhaust the significance of the Kardecist spiritist discourse, but analysis reveals that it is present in both verbal face (according to the analysis we have developed over the ethos in the Kardecist spiritist discourse) and social face (according to the reflections on the present spiritist institutions) of this discourse, becoming thus one of the keys to its reading